Basophil-derived amphiregulin is essential for UVB irradiation-induced immune suppression - Meulenbroeks, Chantal; Van Weelden, Huib; Schwartz, Christian; Vöhringer, David; Redegeld, Frank A. M.; Rutten, Victor P. M. G.; Willemse, Ton; Sijts, Alice J. A. M.; Zaiss, Dietmar M. W. (Journal of Investigative Dermatology, 2015)
UVB irradiation (290-320 nm) is used to treat skin diseases like psoriasis and atopic dermatitis, and is known to suppress contact hypersensitivity (CHS) reactions in mouse models. Regulatory T cells (Treg cells) have been shown to be responsible for this UVB-induced suppression of CHS. The epidermal growth factor (EGF)-like growth factor amphiregulin (AREG) engages EGFR on Treg cells and, in different disease models, it was shown that mast cell-derived AREG is essential for optimal Treg cell function in vivo. Here we determined whether AREG has a role in UVB-induced, Treg cell-mediated suppression of CHS reactions in the skin. Our data show that AREG is essential for UVB-induced CHS suppression. In contrast to the general assumption, however, mast cells were dispensable for UVB-induced immune suppression, whereas basophil-derived AREG was essential. These data reveal, to our knowledge, a previously unreported function for basophils in the homeostasis of immune responses in the skin. Basophils thus fulfill a dual function: they contribute to the initiation of effective type 2 immune responses and, by enhancing the suppressive capacity of local Treg cell populations, also to local immune regulation in the skin.
EVALuna2:25862

Basophil-mediated protection against gastrointestinal helminths requires IgE-induced cytokine secretion - Schwartz, Christian; Turqueti-Neves, Adriana; Hartmann, Susanne; Yu, Philipp; Nimmerjahn, Falk; Vöhringer, David (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Basophils orchestrate protection against reinfections with gastrointestinal helminths and ticks, but the underlying mechanisms remain elusive. We investigated the role of Fc receptors on basophils, the antibody isotypes IgG1 and IgE, and basophil-derived IL-4/IL-13 during challenge infections with Heligmosomoides polygyrus and Nippostrongylus brasiliensis. Using mixed bone marrow chimeras, we found that activating Fc receptors on basophils were required for protective immunity but not for regulation of basophil homeostasis. Furthermore, rapid worm expulsion was impaired in IgE-deficient but not in IgG1-deficient mice. Basophils promoted the recruitment of other effector cells into the small intestine and induced expression of the antihelminthic proteins resistin-like molecule ? and mucin 5ac. Selective deletion of IL-4/IL-13 in basophils resulted in impaired worm expulsion. Collectively, our results indicate that IgE-mediated activation of basophils and the release of basophil-derived IL-4/IL-13 are critical steps in protective immunity against helminths. Therefore, development of effective vaccines against helminths should consider boosting the IL-4/IgE/basophil axis of the immune system.
EVALuna2:25872

Basophils are dispensable for the recovery of gross locomotion after spinal cord hemisection injury - Geurts, Nathalie; Vangansewinkel, Tim; Lemmens, Stefanie; Nelissen, Sofie; Geboes, Lies; Schwartz, Christian; Vöhringer, David; Hendrix, Sven (Journal of Leukocyte Biology, 2015)
Basophils are the smallest population of granulocytes found in the circulation. They have crucial and nonredundant roles in allergic disorders, in protection from parasite infections, in autoimmunity, and in the regulation of type 2 immunity. They share phenotypic and functional properties with mast cells, which exert substantial protective effects after traumatic brain injury and spinal cord injury, although they are considered one of the most proinflammatory cell types in the body. In contrast, the in vivo functions of basophils in central nervous system trauma are still obscure and not well studied. In this study, we show that by comparing spinal cord injury in wild type vs. basophil-deficient Mcpt8Cre transgenic mice, the locomotor recovery is not affected in mice depleted in basophils. In addition, no substantial differences were observed in the lesion size and in the astrocytic and macrophage/microglia reaction between both mouse strains. Hence, despite the multiple properties shared with mast cells, these data show, for the first time, to our knowledge, that basophils are dispensable for the functional recovery process after hemisection injury to the spinal cord in mice.
EVALuna2:25876

Basophils: important emerging players in allergic and anti-parasite responses. - Schwartz, Christian; Vöhringer, David (Bioessays, 2011)

Basophils in inflammation - Schwartz, Christian; Eberle, Jörg; Vöhringer, David (European Journal of Pharmacology, 2015)
Basophils are functionally closely related to mast cells. Both cell types express the high-affinity IgE receptor (Fc?RI) and rapidly release preformed mediator from intracellular stores upon IgE-mediated activation. However, in contrast to mast cells basophils finish their maturation in the bone marrow and have a lifespan of only 2-3 days. Basophil numbers increase in response to IL-3 or TSLP and migrate into tissues to promote type 2 immune responses. Here we review recent advances regarding the pro- and anti-inflammatory functions of basophils in murine models and human allergic inflammation of the skin, lung and intestine.
EVALuna2:25875

Break on through: The role of innate immunity and barrier defence in atopic dermatitis and psoriasis - Hawerkamp, Heike C.; Caoimhe, Fahy; Fallon, Padraic G.; Schwartz, Christian (Skin Health and Disease, 2022)
The human skin can be affected by a multitude of diseases including inflammatory conditions such as atopic dermatitis and psoriasis. Here, we describe how skin barrier integrity and immunity become dysregulated during these two most common inflammatory skin conditions. We summarise recent advances made in the field of the skin innate immune system and its interaction with adaptive immunity. We review gene variants associated with atopic dermatitis and psoriasis that affect innate immune mechanisms and skin barrier integrity. Finally, we discuss how current and future therapies may affect innate immune responses and skin barrier integrity in a generalized or more targeted approach in order to ameliorate disease in patients.<br

Concerted activity of IgG1 antibodies and IL-4/IL-25-dependent effector cells trap helminth larvae in the tissues following vaccination with defined secreted antigens, providing sterile immunity to challenge infection - Hewitson, James P.; Filbey, Kara J.; Bieren, Julia Esser-Von; Camberis, Mali; Schwartz, Christian; Murray, Janice; Reynolds, Lisa A.; Blair, Natalie; Robertson, Elaine; Harcus, Yvonne; Boon, Louis; Huang, Stanley Ching-Cheng; et al. (PLoS Pathogens, 2015)
Over 25% of the world's population are infected with helminth parasites, the majority of which colonise the gastrointestinal tract. However, no vaccine is yet available for human use, and mechanisms of protective immunity remain unclear. In the mouse model of Heligmosomoides polygyrus infection, vaccination with excretory-secretory (HES) antigens from adult parasites elicits sterilising immunity. Notably, three purified HES antigens (VAL-1, -2 and -3) are sufficient for effective vaccination. Protection is fully dependent upon specific IgG1 antibodies, but passive transfer confers only partial immunity to infection, indicating that cellular components are also required. Moreover, immune mice show greater cellular infiltration associated with trapping of larvae in the gut wall prior to their maturation. Intra-vital imaging of infected intestinal tissue revealed a four-fold increase in extravasation by LysM+GFP+ myeloid cells in vaccinated mice, and the massing of these cells around immature larvae. Mice deficient in FcR? chain or C3 complement component remain fully immune, suggesting that in the presence of antibodies that directly neutralise parasite molecules, the myeloid compartment may attack larvae more quickly and effectively. Immunity to challenge infection was compromised in IL-4R?- and IL-25-deficient mice, despite levels of specific antibody comparable to immune wild-type controls, while deficiencies in basophils, eosinophils or mast cells or CCR2-dependent inflammatory monocytes did not diminish immunity. Finally, we identify a suite of previously uncharacterised heat-labile vaccine antigens with homologs in human and veterinary parasites that together promote full immunity. Taken together, these data indicate that vaccine-induced immunity to intestinal helminths involves IgG1 antibodies directed against secreted proteins acting in concert with IL-25-dependent Type 2 myeloid effector populations.
EVALuna2:25873

Conditional IL-4/IL-13-deficient mice reveal a critical role of innate immune cells for protective immunity against gastrointestinal helminths - Oeser, Katharina; Schwartz, Christian; Vöhringer, David (Mucosal Immunology, 2015)
Approximately one-third of the world population is infected with gastrointestinal helminths. Studies in mouse models have demonstrated that the cytokines interleukin (IL)-4 and IL-13 are essential for worm expulsion, but the critical cellular source of these cytokines is poorly defined. Here, we compared the immune response to Nippostrongylus brasiliensis in wild-type, T cell-specific IL-4/IL-13-deficient and general IL-4/IL-13-deficient mice. We show that T cell-derived IL-4/IL-13 promoted T helper 2 (Th2) polarization in a paracrine manner, differentiation of alternatively activated macrophages, and tissue recruitment of innate effector cells. However, innate IL-4/IL-13 played the critical role for induction of goblet cell hyperplasia and secretion of effector molecules like Mucin5ac and RELM? in the small intestine. Surprisingly, T cell-specific IL-4/IL-13-deficient and wild-type mice cleared the parasite with comparable efficiency, whereas IL-4/IL-13-deficient mice showed impaired expulsion. These findings demonstrate that IL-4/IL-13 produced by cells of the innate immune system is required and sufficient to initiate effective type 2 immune responses resulting in protective immunity against N. brasiliensis.
EVALuna2:25865

CreER(T2) expression from within the c-Kit gene locus allows efficient inducible gene targeting in and ablation of mast cells - Heger, Klaus; Seidler, Barbara; Vahl, J. Christoph; Schwartz, Christian; Kober, Maike; Klein, Sabine; Vöhringer, David; Saur, Dieter; Schmidt-Supprian, Marc (European Journal of Immunology, 2014)
Mast cells are abundantly situated at contact sites between the body and its environment, such as the skin and, especially during certain immune responses, at mucosal surfaces. They mediate allergic reactions and degrade toxins as well as venoms. However, their roles during innate and adaptive immune responses remain controversial and it is likely that major functions remain to be discovered. Recent developments in mast cell-specific conditional gene targeting in the mouse promise to enhance our understanding of these fascinating cells. To complete the genetic toolbox to study mast cell development, homeostasis and function, it is imperative to inducibly manipulate their gene expression. Here, we report the generation of a novel knock-in mouse line expressing a tamoxifen-inducible version of the Cre recombinase from within the endogenous c-Kit locus. We demonstrate highly efficient and specific inducible expression of a fluorescent reporter protein in mast cells both in vivo and in vitro. Furthermore, induction of diphtheria toxin A expression allowed selective and efficient ablation of mast cells at various anatomical locations, while other hematopoietic cells remain unaffected. This novel mouse strain will hence be very valuable to study mast cell homeostasis and how specific genes influence their functions in physiology and pathology.
EVALuna2:25867

Determining Coreceptor Expression and Function in Murine ILC2 Through Flow Cytometry Characterization and Coculture Techniques - Schwartz, Christian; Fallon, Padraic G. (Methods in Molecular Biology, 2020)
Group 2 innate lymphoid cells are important innate effectors and regulators of adaptive immunity in response to parasitic infections and allergic inflammation. Their low frequency in vivo during steady state condition may complicate research on the cells. During type 2 biased immune responses they are activated, increase in frequency and release cytokines as well as regulate T cell functions through direct interactions including MHC class II–T cell receptor interactions. Importantly, coreceptors significantly influence the ILC2-T cell cross talk and shape the adaptive immune response. Here, we provide an experimental framework to study the function of coreceptors expressed on tissue ILC2. In brief, we describe flow cytometric analysis of the coreceptor of interest, the isolation and culture of mouse pulmonary ILC2 and splenic T cells, as well as approaches to manipulate their coculture. Finally, downstream readout options are outlined.
CRIS-Team Scopus Importer:2020-03-24
Keywords: Coculture; Cytokines; ILC2; Innate immunity; MHC2; Regulation; Stimulation; T helper cells; Transcription factors; Type 2 immune response

Dysregulated skin barrier function in Tmem79 mutant mice promotes IL-17A-dependent spontaneous skin and lung inflammation - Saunders, Sean P.; Floudas, Achilleas; Moran, Tara; Byrne, Ciara M.; Rooney, Michael D.; Fahy, Caoimhe M.R.; Geoghegan, Joan A.; Iwakura, Yoichiro; Fallon, Padraic G.; Schwartz, Christian (Allergy, 2020)
Background: Atopic dermatitis (AD) is associated with a dysregulation of the skin barrier and may predispose to the development of secondary allergic conditions, such as asthma. Tmem79ma/ma mice harbor a mutation in the gene encoding Transmembrane Protein 79 (or Mattrin), which has previously been associated with AD. As a result of the Tmem79 gene mutation, these mice have a defective skin barrier and develop spontaneous skin inflammation. In this study, Tmem79ma/ma mice were assessed for the underlying immunological response in the development of spontaneous skin and lung inflammation. Methods: Development of spontaneous skin and lung inflammation in Tmem79ma/ma mice was analyzed. We further investigated susceptibility to cutaneous Staphylococcus aureus infection. Tmem79ma/ma were crossed to IL-17A-deficient mice to address the contribution of IL-17A to spontaneous skin and lung disease. Results: Tmem79ma/ma mice developed IL-17A-dependent spontaneous AD-like inflammation and were refractory to S aureus infection. Mutant mice progressed to airway inflammation subsequent to the occurrence of dermatitis. The progression from skin to lung disease is dependent on adaptive immunity and is facilitated by cutaneous expansion of Th17 and TCRγδ T cells. Conclusion: Mice lacking Tmem79/Mattrin expression have a defective skin barrier. In adulthood, these mice develop dermatitis with secondary progression to lung inflammation. The development of skin and lung inflammation is IL-17A-dependent and mediated by TCRγδ T cells.
CRIS-Team Scopus Importer:2020-07-31
Keywords: cutaneous inflammation; interleukin-17A; lung inflammation; skin barrier; Tmem79

Eosinophil-specific deletion of I?B? in mice reveals a critical role of NF-?B-induced Bcl-xL for inhibition of apoptosis - Schwartz, Christian; Willebrand, Ralf; Huber, Silke; Rupec, Rudolf A.; Wu, Davina; Locksley, Richard; Vöhringer, David (Blood, 2015)
Eosinophils are associated with type 2 immune responses to allergens and helminths. They release various proinflammatory mediators and toxic proteins on activation and are therefore considered proinflammatory effector cells. Eosinophilia is promoted by the cytokines interleukin (IL)-3, IL-5, and granulocyte macrophage-colony-stimulating factor (GM-CSF) and can result from enhanced de novo production or reduced apoptosis. In this study, we show that only IL-5 induces differentiation of eosinophils from bone marrow precursors, whereas IL-5, GM-CSF, and to a lesser extent IL-3 promote survival of mature eosinophils. The receptors for these cytokines use the common ? chain, which serves as the main signaling unit linked to signal transducer and activator of transcription 5, p38 mitogen-activated protein kinase, and nuclear factor (NF)-?B pathways. Inhibition of NF-?B induced apoptosis of in vitro cultured eosinophils. Selective deletion of I?B? in vivo resulted in enhanced expression of Bcl-xL and reduced apoptosis during helminth infection. Retroviral overexpression of Bcl-xL promoted survival, whereas pharmacologic inhibition of Bcl-xL in murine or human eosinophils induced rapid apoptosis. These results suggest that therapeutic strategies targeting Bcl-xL in eosinophils could improve health conditions in allergic inflammatory diseases.
EVALuna2:25866

Epidermal Growth Factor Receptor Expression Licenses Type-2 Helper T Cells to Function in a T Cell Receptor-Independent Fashion. - Minutti, Carlos M.; Drube, Sebastian; Blair, Natalie; Schwartz, Christian; Mccrae, Jame C.; Mckenzie, Andrew N.; Kamradt, Thomas; Mokry, Michal; Coffer, Paul J.; Sibilia, Maria; Sijts, Alice J.; Fallon, Padraic G.; et al. (Immunity, 2017)
Gastro-intestinal helminth infections trigger the release of interleukin-33 (IL-33), which induces type-2 helper T cells (Th2 cells) at the site of infection to produce IL-13, thereby contributing to host resistance in a T cell receptor (TCR)-independent manner. Here, we show that, as a prerequisite for IL-33-induced IL-13 secretion, Th2 cells required the expression of the epidermal growth factor receptor (EGFR) and of its ligand, amphiregulin, for the formation of a signaling complex between T1/ST2 (the IL-33R) and EGFR. This shared signaling complex allowed IL-33 to induce the EGFR-mediated activation of the MAP-kinase signaling pathway and consequently the expression of IL-13. Lack of EGFR expression on T cells abrogated IL-13 expression in infected tissues and impaired host resistance. EGFR expression on Th2 cells was TCR-signaling dependent, and therefore, our data reveal a mechanism by which antigen presentation controls the innate effector function of Th2 cells at the site of inflammation.
Keywords: gastro-intestinal helminth infections; type-2 helper T cells; interleukin-13; interleukin-33; TCR-independent IL-13 secretion; cytokine signaling

Functional impact of reverse signalling via PD-L1 in ILC2 during type 2 immune responses - Bailer, Moritz; Deinzer, Andrea; Schmidt, Viviane; Schwartz, Christian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Helminth Modulation of Lung Inflammation. - Schwartz, Christian; Hams, Emily; Fallon, Padraic G. (Trends in Parasitology, 2018)
Parasitic helminths must establish chronic infections to complete their life cycle and therefore are potent modulators of multiple facets of host physiology. Parasitic helminths have coevolved with humans to become arguably master selectors of our immune system, whereby they have impacted on the selection of genes with beneficial mutations for both host and parasite. While helminth infections of humans are a significant health burden, studies have shown that helminths or helminth products can alter susceptibility to unrelated infectious or inflammatory diseases. This has generated interest in the use of helminth infections or molecules as therapeutics. In this review, we focus on the impact of helminth infections on pulmonary immunity, especially with regard to homeostatic lung function, pulmonary viral and bacterial (co)infections, and asthma.

High salt reduces the activation of IL-4- and IL-13-stimulated macrophages - Binger, Katrina J.; Gebhardt, Matthias; Heinig, Matthias; Rintisch, Carola; Schröder, Agnes; Neuhofer, Wolfgang; Hilgers, Karl Friedrich; Manzel, Arndt; Schwartz, Christian; Kleinewietfeld, Markus; Voelkl, Jakob; Schatz, Valentin; et al. (Journal of Clinical Investigation, 2015)
A high intake of dietary salt (NaCl) has been implicated in the development of hypertension, chronic inflammation, and autoimmune diseases. We have recently shown that salt has a proinflammatory effect and boosts the activation of Th17 cells and the activation of classical, LPS-induced macrophages (M1). Here, we examined how the activation of alternative (M2) macrophages is affected by salt. In stark contrast to Th17 cells and M1 macrophages, high salt blunted the alternative activation of BM-derived mouse macrophages stimulated with IL-4 and IL-13, M(IL-4+IL-13) macrophages. Salt-induced reduction of M(IL-4+IL-13) activation was not associated with increased polarization toward a proinflammatory M1 phenotype. In vitro, high salt decreased the ability of M(IL-4+IL-13) macrophages to suppress effector T cell proliferation. Moreover, mice fed a high salt diet exhibited reduced M2 activation following chitin injection and delayed wound healing compared with control animals. We further identified a high salt-induced reduction in glycolysis and mitochondrial metabolic output, coupled with blunted AKT and mTOR signaling, which indicates a mechanism by which NaCl inhibits full M2 macrophage activation. Collectively, this study provides evidence that high salt reduces noninflammatory innate immune cell activation and may thus lead to an overall imbalance in immune homeostasis.
EVALuna2:3819

Identification of murine basophils by flow cytometry and histology - Schwartz, Christian; Vöhringer, David (Methods in Molecular Biology, 2014)
Here we describe how murine basophils can be detected in vivo by flow cytometry and immunofluorescence staining. Basophils constitute a homogeneous population of CD4(-)CD19(-)CD49b(+)IgE(+) cells in flow cytometric analysis. When IgE levels are low one can also use anti-Fc?RI or anti-CD200R3 antibodies instead of anti-IgE. For immunofluorescence staining we use an anti-Mcpt8 antibody since Mcpt8 is a specific marker for murine basophils. We describe how to prepare the tissue to cut cryo-sections and how to perform the staining using a tyramide-based amplification kit.
EVALuna2:25874

Identification of Murine Basophils by Flow Cytometry and Histology. - Schwartz, Christian; Vöhringer, David (Methods in Molecular Biology, 2020)
Here, we describe how murine basophils can be detected in vivo by flow cytometry and immunofluorescence staining. Basophils constitute a homogeneous population of CD4-CD19-CD49b+IgE+ cells in flow cytometric analysis. When IgE levels are low, one can also use anti-FcεRI or anti-CD200R3 antibodies instead of anti-IgE. For immunofluorescence staining, we use an anti-Mcpt8 antibody since Mcpt8 is a specific marker for murine basophils. We describe how to prepare the tissue to cut cryo-sections and how to perform the staining using a tyramide-based amplification kit.
EVALuna2:419002

IL-17 Receptor A Maintains and Protects the Skin Barrier To Prevent Allergic Skin Inflammation. - Floudas, Achilleas; Saunders, Sean P.; Moran, Tara; Schwartz, Christian; Hams, Emily; Fitzgerald, Denise C.; Johnston, James A.; Ogg, Graham S.; Mckenzie, Andrew N.; Walsh, Patrick T.; Fallon, Padraic G. (Journal of Immunology, 2017)
mice was dependent on TSLP, but not the other alarmins IL-25 and IL-33. The associated skin inflammation was mediated by IL-5-expressing pathogenic effector Th2 cells and was independent of TCRγδ T cells and IL-22. An absence of IL-17RA in nonhematopoietic cells, but not in the hematopoietic cells, was required for the development of spontaneous skin inflammation. Skin microbiome dysbiosis developed in the absence of IL-17RA, with antibiotic intervention resulting in significant amelioration of skin inflammation and reductions in skin-infiltrating pathogenic effector Th2 cells and TSLP. This study describes a previously unappreciated protective role for IL-17RA signaling in regulation of the skin barrier and maintenance of skin immune homeostasis.

IL-25 and type 2 innate lymphoid cells induce pulmonary fibrosis - Hams, Emily; Armstrong, Michelle E.; Barlow, Jillian L.; Saunders, Sean P.; Schwartz, Christian; Cooke, Gordon; Fahy, Ruairi J.; Crotty, Thomas B.; Hirani, Nikhil; Flynn, Robin J.; Vöhringer, David; Mckenzie, Andrew N. J.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Disease conditions associated with pulmonary fibrosis are progressive and have a poor long-term prognosis with irreversible changes in airway architecture leading to marked morbidity and mortalities. Using murine models we demonstrate a role for interleukin (IL)-25 in the generation of pulmonary fibrosis. Mechanistically, we identify IL-13 release from type 2 innate lymphoid cells (ILC2) as sufficient to drive collagen deposition in the lungs of challenged mice and suggest this as a potential mechanism through which IL-25 is acting. Additionally, we demonstrate that in human idiopathic pulmonary fibrosis there is increased pulmonary expression of IL-25 and also observe a population ILC2 in the lungs of idiopathic pulmonary fibrosis patients. Collectively, we present an innate mechanism for the generation of pulmonary fibrosis, via IL-25 and ILC2, that occurs independently of T-cell-mediated antigen-specific immune responses. These results suggest the potential of therapeutically targeting IL-25 and ILC2 for the treatment of human fibrotic diseases.
EVALuna2:25861

ILC2s regulate adaptive Th2 cell functions via PD-L1 checkpoint control. - Schwartz, Christian; Khan, Adnan R.; Floudas, Achilleas; Saunders, Sean P.; Hams, Emily; Rodewald, Hans-Reimer; Mckenzie, Andrew N. J.; Fallon, Padraic G. (Journal of Experimental Medicine, 2017)
Our results identify a novel PD-L1-controlled mechanism for type 2 polarization, with ILC2s mediating an innate checkpoint to control adaptive T helper responses, which has important implications for the treatment of type 2 inflammation.

Innate PD-L1 limits T cell-mediated adipose tissue inflammation and ameliorates diet-induced obesity - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, H. C.; Hams, E.; Bayerlein, Jasmin; Roeger, O.; Bailer, Moritz; Krautz, Christian; El Gendy, Amr; Elshafei, Moustafa; Heneghan, H. M.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Innate PD-L1 limits T cell-mediated adipose tissue inflammation and ameliorates diet-induced obesity - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; Elgendy, Amr; Elshafei, Moustafa; Heneghan, Helen M.; et al. (Science Translational Medicine, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.
CRIS-Team Scopus Importer:2022-03-25

Innate PD-L1 limits T cell mediated adipose tissue inflammation - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; El Gendy, Amr; Elshafei, Moustafa; Hogan, Andrew E.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.<br
CRIS-Team WoS Importer:2022-03-11

Interleukin 33: an innate alarm for adaptive responses beyond Th2 immunity-emerging roles in obesity, intestinal inflammation, and cancer. - Schwartz, Christian; O'Grady, Katie; Lavelle, Ed C.; Fallon, Padraic G. (European Journal of Immunology, 2016)
Interleukin (IL)-33, a member of the IL-1 family, was originally described in 2005 as a potent initiator of type 2 immunity found during allergic inflammation and parasitic infections. IL-33 has been shown to play important and potent roles bridging innate and adaptive immunity in the regulation of tissue homeostasis, injury, and repair. Recent discoveries have extended the range of functions for IL-33 beyond type 2 conditions and its role as an alarmin at barrier sites, with emerging central roles for IL-33 in T-cell regulation, obesity, viral and tumor immunity. Here, we review the recent advances on how IL-33 activity is regulated, its immunomodulatory properties on innate and adaptive cells, and the newly discovered roles of IL-33 in obesity, intestinal inflammation, and tumorigenesis.

Obesity impairs pulmonary type 2 immunity during helminth infection - Deinzer, Andrea; Schmidt, Viviane; Schwartz, Christian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Obesity-Mediated Immune Modulation: One Step Forward, (Th)2 Steps Back - Schmidt, Viviane; Hogan, Andrew E.; Fallon, Padraic G.; Schwartz, Christian (Frontiers in Immunology, 2022)
Over the past decades, the relationship between the immune system and metabolism has become a major research focus. In this arena of immunometabolism the capacity of adipose tissue to secrete immunomodulatory molecules, including adipokines, within the underlying low-grade inflammation during obesity brought attention to the impact obesity has on the immune system. Adipokines, such as leptin and adiponectin, influence T cell differentiation into different T helper subsets and their activation during immune responses. Furthermore, within the cellular milieu of adipose tissue nutrient availability regulates differentiation and activation of T cells and changes in cellular metabolic pathways. Upon activation, T cells shift from oxidative phosphorylation to oxidative glycolysis, while the differential signaling of the kinase mammalian target of rapamycin (mTOR) and the nuclear receptor PPAR gamma, amongst others, drive the subsequent T cell differentiation. While the mechanisms leading to a shift from the typical type 2-dominated milieu in lean people to a Th1-biased pro-inflammatory environment during obesity are the subject of extensive research, insights on its impact on peripheral Th2-dominated immune responses become more evident. In this review, we will summarize recent findings of how Th2 cells are metabolically regulated during obesity and malnutrition, and how these states affect local and systemic Th2-biased immune responses.
CRIS-Team WoS Importer:2022-07-29

Opposing functions of thymic stromal lymphopoietin-responsive basophils and dendritic cells in a mouse model of atopic dermatitis - Schwartz, Christian; Eberle, Jörg; Hoyler, Thomas; Diefenbach, Andreas; Lechmann, Matthias; Vöhringer, David (Journal of Allergy and Clinical Immunology, 2016)
EVALuna2:25878

Retinoic Acid-Related Orphan Receptor α Is Required for Generation of Th2 Cells in Type 2 Pulmonary Inflammation - Roberts, Joseph; Chevalier, Anne; Hawerkamp, Heike C.; Yeow, Aoife; Matarazzo, Laura; Schwartz, Christian; Hams, Emily; Fallon, Padraic G. (Journal of Immunology, 2023)
The transcription factor retinoic acid-related orphan receptor α (RORα) is important in regulating several physiological functions, such as cellular development, circadian rhythm, metabolism, and immunity. In two in vivo animal models of type 2 lung inflammation, Nippostrongylus brasiliensis infection and house dust mite (HDM) sensitization, we show a role for Rora in Th2 cellular development during pulmonary inflammation. N. brasiliensis infection and HDM challenge induced an increase in frequency of Rora-expressing GATA3+CD4 T cells in the lung. Using staggerer mice, which have a ubiquitous deletion of functional RORα, we generated bone marrow chimera mice, and we observed a delayed worm expulsion and reduced frequency in the expansion of Th2 cells and innate lymphoid type 2 cells (ILC2s) in the lungs after N. brasiliensis infection. ILC2-deficient mouse (Rorafl/flIl7raCre) also had delayed worm expulsion with associated reduced frequency of Th2 cells and ILC2s in the lungs after N. brasiliensis infection. To further define the role for Rora-expressing Th2 cells, we used a CD4-specific Rora-deficient mouse (Rorafl/flCD4Cre), with significantly reduced frequency of lung Th2 cells, but not ILC2, after N. brasiliensis infection and HDM challenge. Interestingly, despite the reduction in pulmonary Th2 cells in Rorafl/flCD4Cre mice, this did not impact the expulsion of N. brasiliensis after primary and secondary infection, or the generation of lung inflammation after HDM challenge. This study demonstrates a role for RORα in Th2 cellular development during pulmonary inflammation that could be relevant to the range of inflammatory diseases in which RORα is implicated.
CRIS-Team Scopus Importer:2023-08-18

Schistosoma "Eggs-Iting" the Host: Granuloma Formation and Egg Excretion. - Schwartz, Christian; Fallon, Padraic G. (Frontiers in Immunology, 2018)
eggs laid in vasculature must usurp immunity to induce regulated inflammation, to facilitate extravasation through the intestinal wall and to be expelled in the feces. We highlight the roles of immune cell populations, stromal factors, and egg secretions in the process of egg excretion to provide a comprehensive overview of the current state of knowledge regarding a vastly unexplored mechanism.

Schistosoma mansoni Worm Infection Regulates the Intestinal Microbiota and Susceptibility to Colitis. - Floudas, Achilleas; Aviello, Gabriella; Schwartz, Christian; Jeffery, Ian B.; O'Toole, Paul W.; Fallon, Padraic G. (Infection and Immunity, 2019)
worm infection modulates the host's immune system and suppresses bystander colitis while limiting dysbiosis of the host's intestinal microbiome during infection.

Spontaneous atopic dermatitis in mice with a defective skin barrier is independent of ILC2 and mediated by IL-1β - Schwartz, Christian; Moran, Tara; Saunders, Sean P.; Kaszlikowska, Agnieszka; Floudas, Achilleas; Bom, Joana; Nunez, Gabriel; Iwakura, Yoichiro; O’Neill, Luke; Irvine, Alan D.; McKenzie, Andrew N.J.; Ogg, Graham; et al. (Allergy, 2019)
Background: Atopic dermatitis (AD) is one of the most common skin diseases with a multifactorial etiology. Mutations leading to loss of skin barrier function are associated with the development of AD with group 2 innate lymphoid cells (ILC2) promoting acute skin inflammation. Filaggrin-mutant (Flg ft/ft ) mice develop spontaneous skin inflammation accompanied by an increase in skin ILC2 numbers, IL-1β production, and other cytokines recapitulating human AD. Here, we investigated the role of ILC2, effector cytokines, inflammasome activation, and mast cell function on the development of chronic AD-like inflammation in mice. Methods: Mice with a frameshift mutation in the filaggrin gene develop spontaneous dermatitis. Flg ft/ft mice were crossed to cell- or cytokine-deficient mouse strains, or bred under germ-free conditions. Skin inflammation was scored, and microbiome composition was analyzed. Skin protein expression was measured by multiplex immunoassay. Infiltrating cells were analyzed by flow cytometry. Results: Wild-type and Flg ft/ft mice significantly differ in their microbiome composition. Furthermore, mutant mice do not develop skin inflammation under germ-free conditions. ILC2 deficiency did not ameliorate chronic dermatitis in Flg ft/ft mice, which was also independent of IL-4, IL-5, IL-9, IL-13, IL-17A, and IL-22. Inflammation was independent of NLRP3 inflammasome activation but required IL-1β and IL-1R1-signaling. Mechanistically, IL-1β promoted hyperactivation of IL-1R1-expressing mast cells. Treatment with anti-IL-1β-antibody alleviated dermatitis exacerbation, while antibiotic intervention ameliorated dermatitis in neonatal mice but not in adults with established inflammation. Conclusions: In summary, we identified a critical role for the microbiome and IL-1β mediating chronic inflammation in mice with an impaired skin barrier.
CRIS-Team Scopus Importer:2019-05-17
Keywords: atopic dermatitis; filaggrin; IL-1β; innate lymphoid cells; microbiome

T cell-derived IL-4/IL-13 protects mice against fatal Schistosoma mansoni infection independently of basophils - Schwartz, Christian; Oeser, Katharina; Da Costa, Clarissa Prazeres; Layland, Laura E.; Vöhringer, David (Journal of Immunology, 2014)
Schistosomiasis is a severe and chronic disease caused by the parasitic trematode Schistosoma mansoni after deposition of eggs in the liver and intestines. The immune response to S. mansoni eggs is characterized by increased Th2 cells, eosinophilia, and high serum IgE levels. Granulomas are formed around the eggs to protect the organs against tissue damage caused by toxic products that are secreted from the eggs. Egg-derived components have further been shown to activate the IgE-mediated release of IL-4 and IL-13 from basophils, suggesting that basophils could be involved in protection against a fatal course of infection. Using T cell-specific IL-4/IL-13-deficient mice and basophil-deficient Mcpt8Cre mice, we determined the contribution of Th2 cells and basophils for protective immunity against S. mansoni egg-induced pathology during the patent stage of infection. Our results demonstrate that T cell-derived IL-4/IL-13 was essential for granuloma formation, IgE production, basophilia, differentiation of alternatively activated macrophages, and protection against fatal infection. Although basophils were recruited into liver granulomas, they appeared to be dispensable as a source of IL-4/IL-13 both for differentiation of Th2 cells and for prevention of weight loss and mortality.
EVALuna2:25868

The Extracellular Domains of IgG1 and T Cell-Derived IL-4/IL-13 Are Critical for the Polyclonal Memory IgE Response In Vivo - Turqueti-Neves, Adriana; Otte, Manuel; Schwartz, Christian; Schmitt, Michaela; Lindner, Cornelia; Pabst, Oliver; Yu, Philipp; Vöhringer, David (Plos Biology, 2015)
IgE-mediated activation of mast cells and basophils contributes to protective immunity against helminths but also causes allergic responses. The development and persistence of IgE responses are poorly understood, which is in part due to the low number of IgE-producing cells. Here, we used next generation sequencing to uncover a striking overlap between the IgE and IgG1 repertoires in helminth-infected or OVA/alum-immunized wild-type BALB/c mice. The memory IgE response after secondary infection induced a strong increase of IgE+ plasma cells in spleen and lymph nodes. In contrast, germinal center B cells did not increase during secondary infection. Unexpectedly, the memory IgE response was lost in mice where the extracellular part of IgG1 had been replaced with IgE sequences. Adoptive transfer studies revealed that IgG1+ B cells were required and sufficient to constitute the memory IgE response in recipient mice. T cell-derived IL-4/IL-13 was required for the memory IgE response but not for expansion of B cells from memory mice. Together, our results reveal a close relationship between the IgE and IgG1 repertoires in vivo and demonstrate that the memory IgE response is mainly conserved at the level of memory IgG1+ B cells. Therefore, targeting the generation and survival of allergen-specific IgG1+ B cells could lead to development of new therapeutic strategies to treat chronic allergic disorders.
EVALuna2:25871

The high and lows of type 2 asthma and mouse models - Fallon, Padraic G.; Schwartz, Christian (Journal of Allergy and Clinical Immunology, 2019)
CRIS-Team Scopus Importer:2019-12-31
Keywords: allergic airway disease; Asthma; mouse models; type 2 inflammation